2010
DOI: 10.3928/01913913-20100218-02
|View full text |Cite
|
Sign up to set email alerts
|

Coats' Disease and Neovascular Glaucoma in a Child With Neurofibromatosis

Abstract: This report describes an extremely rare case of Coats' disease and neovascular glaucoma in a child with neurofibromatosis 1. Intraocular pressure control and vision restoration were achieved with intravitreal injection with bevacizumab, hemiretinal laser photocoagulation, peripheral retinal cryotherapy, and trabeculectomy with mitomycin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Cryotherapy is preferred in lesions in the far periphery or with massive exudation [2]. IVTA [4,5] and anti-VEGF agents have been used alone [6,7] or with laser [8][9][10][11][12][13][14] primarily in children with Coats' disease to improve resorption of subretinal fluid and lipid exudates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cryotherapy is preferred in lesions in the far periphery or with massive exudation [2]. IVTA [4,5] and anti-VEGF agents have been used alone [6,7] or with laser [8][9][10][11][12][13][14] primarily in children with Coats' disease to improve resorption of subretinal fluid and lipid exudates.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed that laser therapy with adjunctive intravitreal injection has been performed at varying time periods ranging from the time of injection [9,14] to 6 weeks following injection [8,10,12,15]. The optimal time period between intravitreal injection and laser treatment is unclear, but we feel that this should be judged clinically on an individual basis by the response to anti-VEGF treatment [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of posterior segment vascular abnormalities including a variety of tumors have been reported in the literature in patients with NF1, mostly as single case reports, [8][9][10][11][12] the association of these abnormalities with neovascularization of the iris and neovascular glaucoma has only been described in a handful of cases. [3][4][5][6][7] Neovascular glaucoma in children is rare but NF1 needs to be considered among the possible causes in the pediatric age group as pointed out by case 1 in this study and the other cases reported in the literature. [3][4][5][6][7] Neovascular glaucoma in children is rare but NF1 needs to be considered among the possible causes in the pediatric age group as pointed out by case 1 in this study and the other cases reported in the literature.…”
Section: Discussionmentioning
confidence: 67%
“…It results from a combination of factors that include (1) infiltration of the angle by diffuse neurofibromas, (2) mechanical closure of the angle due to neurofibromatous thickening of the ciliary body, (3) secondary fibrovascular and synechial closure of the angle, (4) congenital angle abnormalities, 1 and (5) endothelialization of the angle attributed to secondary chronic angle closure. [3][4][5][6][7] We report the clinical findings and outcomes in 3 young patients with NF1 who developed iris neovascularization and neovascular glaucoma secondary to retinal vascular abnormalities and describe the histopathologic abnormalities in the enucleated specimen of 1 case. [3][4][5][6][7] We report the clinical findings and outcomes in 3 young patients with NF1 who developed iris neovascularization and neovascular glaucoma secondary to retinal vascular abnormalities and describe the histopathologic abnormalities in the enucleated specimen of 1 case.…”
mentioning
confidence: 99%